RISIKO USAHATANI PADI SAWAH RUMAH TANGGA DI DAERAH IMPENSO PROVINSI SULAWESI TENGAH - Arifuddin Lamusa (Agroland: Jurnal Ilmu-ilmu Pertanian, 2010)
This study aimed to identify the risk of household wetland rice farm production in impenso and non impenso regions in Central Sulawesi Province.  Respondent samples of 250 farmers were randomly chosen.  Data collected through interviews and field note records. The research result showed that coefficient of variance of the rice farm in the impenso region was higher than in the non impenso region suggesting that the risk of the first region was larger than the later.